2019
DOI: 10.1177/1475921719884861
|View full text |Cite
|
Sign up to set email alerts
|

Two spatial association–considered mathematical models for diagnosing the long-term balanced relationship and short-term fluctuation of the deformation behaviour of high concrete arch dams

Abstract: The safety of a high concrete arch dam should be rapidly diagnosed from different angles. Displacement is an actual comprehensive reflection of the arch dam, and it is very important to diagnose the overall deformation behaviour by displacement-based mathematical monitoring models. In this article, based on the spatial association validation of the measured displacement of two high arch dams by the empirical orthogonal function decomposition and the Pearson correlation analysis, two spatial association–conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The influential factors for the dam body displacement at different elevations were determined as follows: For EL172.5, the influential factors were water level (1), air temperature (3), and dam body temperature (17); for EL150.0, they were water level (1), air temperature (3), and dam body temperature (17); for EL115.0, water level (1) and dam body temperature (15); for EL90.0, water level (1) and dam body temperature (10); and for EL57.5, water level (1) and dam body temperature (7). The factors and subfactors for these observation points (Table 5) were employed as parameters for the AI inference models in this study.…”
Section: Factor Analysis and Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influential factors for the dam body displacement at different elevations were determined as follows: For EL172.5, the influential factors were water level (1), air temperature (3), and dam body temperature (17); for EL150.0, they were water level (1), air temperature (3), and dam body temperature (17); for EL115.0, water level (1) and dam body temperature (15); for EL90.0, water level (1) and dam body temperature (10); and for EL57.5, water level (1) and dam body temperature (7). The factors and subfactors for these observation points (Table 5) were employed as parameters for the AI inference models in this study.…”
Section: Factor Analysis and Selectionmentioning
confidence: 99%
“…Then, the three-dimensional finite element analysis was conducted to establish a function mapping the correlation between the actual and measured displacements through a regression method. Wang, Xu 17 established two displacement-based mathematical models to diagnose the overall deformation behavior of a high arch dam.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Therefore, many scholars focus on the set collective innovation of intelligent algorithms and decomposition tools. Wang et al 13 proposed a multipoint hybrid model based on principal component analysis to predict the deformation information of the entire dam. Mata 14 showed that the artificial neural network (ANN) model is an effective method to represent the performance of concrete dam behavior under environment loads.…”
Section: Introductionmentioning
confidence: 99%
“…However, mathematical models are mostly established for single monitoring point and from the single modelling angle of causality, whereas spatial associations of displacements at multiple monitoring points are ignored. 32,33 To solve this problem, data fusion technologies, including the PCA, projection pursuit analysis and entropy, have been used to extract useful information from measured displacements of multiple monitoring points, and special mathematical models or monitoring indexes have been established to determine the overall variation of dam displacement field. [34][35][36][37] To consider the similarity of displacements among multiple monitoring points, Chen et al 38 proposed a spatio-temporal clustering and diagnosis method for concrete arch dams.…”
Section: Introductionmentioning
confidence: 99%